Effects of Triclosan and Biosolids on Microbial Community Composition in an Agricultural Soil. (1st December 2013) - Park, Inmyoung; Zhang, Nannan; Ogunyoku, Temitope A.; Young, Thomas M.; Scow, Kate M.
ABSTRACT: : Triclosan (TCS) is a widely used antimicrobial agent found at high concentrations in biosolids produced during municipal wastewater treatment. The effect of adding TCS, in the presence or absence of biosolids, on the composition of an agricultural soil microbial community was measured using phospholipid fatty acid analysis (PLFA). Most changes observed in microbial community composition were attributable to the addition of biosolids or to the passage of time, with smaller changes due to TCS exposure, regardless of the presence of biosolids. TCS slightly reduced the relative abundance of Gram‐positive and Gram‐negative bacteria and fungi, with or without biosolids. Bacteria were more sensitive than eukaryotes, consistent with the mode of action of TCS, which selectively targets fatty acid synthesis and disrupts cell membranes of bacteria. TCS slightly increased biomarkers of microbial stress, but stress biomarkers were lower in all biosolid treated soils, presumably due to increased availability of nutrients mitigating potential TCS toxicity.